Improve Sewing Skills Vocationally through Zipper Media Video Tutorials for Deaf Children - Nilam Permai Sari; Kasiyati Kasiyati (EDUCATIO : Journal of Education, 2020)
This research is based on observations made when the street vendors at SLB 1 Lima Kaum, this study discusses improving zipper sewing skills for deaf children. The process of learning sewing skills is beneficial for children because learning to sew can improve children's skills so that when a child graduates from school, the child can develop his potential, such as opening his stitches at home or working with other parties. Not all the components of sewing skills can be understood by the child, in the zipper sewing section Children have difficulty in sewing zippers correctly. The use of other media can improve children's skills such as the use of video tutorial media. Video tutorials are learning media in the form of a series of moving images, making sounds, and assembling into a storyline that contains learning messages and is stored in a media. The use of video tutorial media according to researchers is able to improve children's sewing skills, this can be seen in the baseline condition (A) of the child, ie horizontally (=), in conditions of intervention, increasing (+) and final baseline conditions also increasing (+). The results of the study prove that video tutorials can improve zipper sewing skills for deaf children.